Stimulating Innovation Work in Sports in the Republic of Belorussia - O. V. Dodonov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article reveals the notion of innovation work in view of economy methodology and shows its importance for the development of the field of physical training and sports. Key categories of workers were identified, whose interaction could foster the development and introduction of innovation in the given field. The article shows motivators of innovation work and highlights legal base and stimulating factors of innovation work in organizations of physical training and sports in the Republic of Belorussia. The author grouped certain categories of workers in organizations of physical training and sports by job descriptions and tariff grades with regard to key factors characterizing innovation work and demonstrates categories of workers in organization of physical training and sports, whose job descriptions do not include the need to introduce innovation in accordance with their classification. Serious contradictions were revealed between workers’ job descriptions and availability (absence) in them obligations to introduce innovation in organizations of physical training and sports in the Republic of Belorussia. The author put forward key trends aimed at resolving the problem of stimulating workers in organizations of physical training and sports to introduce innovation, which can be settled in legislative area and by specifying contacts between employer and worker.